PENANGGULANGAN KEMISKINAN DI KOTA SERANG DENGAN MENGGUNAKAN CAUSAL LOOP DIAGRAM - weni puja ningrum; Dzulkifli, Dzulkifli; Azaria, Aldyth Kendra; sahrupi; shofa, mohamad jihan (Metode : Jurnal Teknik Industri, 2024)
Poverty is defined as a state in which individuals or groups of people are unable to exercise their basic rights to lead a dignified life. One of the cities in Indonesia is Serang City, located in the province of Banten. Currently, the poverty rate in Serang City has reached as high as 46 thousand households, with 8,799 of them falling into the category of extreme poverty. Based on the data obtained, the poverty line in 2022 is higher than the poverty line in the period 2020-2021. This poverty is due to several main factors, including low education, low income, and a lack of job opportunities. Therefore, this research aims to understand the causes and effects of poverty in Serang City and how to address it. To model the poverty alleviation efforts in Serang City, researchers use the Causal Loop Diagram (CLD) method. Causal Loop Diagram (CLD) is a visual tool used to model and analyze the cause-and-effect relationships between various factors in a system. The data processing results reveal the causes and effects of poverty in Serang City, including unemployment, low education levels, increased mortality rates, crime, limited job opportunities, and restricted healthcare services.